2015
DOI: 10.3390/en81010818
|View full text |Cite
|
Sign up to set email alerts
|

Active Participation of Air Conditioners in Power System Frequency Control Considering Users’ Thermal Comfort

Abstract: Air conditioners have great potential to participate in power system frequency control. This paper proposes a control strategy to facilitate the active participation of air conditioners. For each air conditioner, a decentralized control law is designed to adjust its temperature set point in response to the system frequency deviation. The decentralized control law accounts for the user's thermal comfort that is evaluated by a fuzzy algorithm. The aggregation of air conditioners' response is conducted by using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…However, it is worth noting that the comfort of building occupants should be guaranteed while reducing energy consumption. Temperature and relative humidity are the main factors that influence a human's thermal feelings [33][34][35]. The researchers indicated that the humidity has little effect on the occupants' comfort when the temperature is under suitable conditions.…”
Section: The Proposed Mbcrf Algorithmmentioning
confidence: 99%
“…However, it is worth noting that the comfort of building occupants should be guaranteed while reducing energy consumption. Temperature and relative humidity are the main factors that influence a human's thermal feelings [33][34][35]. The researchers indicated that the humidity has little effect on the occupants' comfort when the temperature is under suitable conditions.…”
Section: The Proposed Mbcrf Algorithmmentioning
confidence: 99%
“…To strike a balance between the accuracy and the computational complexity, the simplified model in [11] is applied in this paper. The frequency response models include the generator, prime mover, and governor.…”
Section: Modelling Of the Frequency Responsementioning
confidence: 99%
“…Emergency load shedding control is an effective measure to ensure the safe and stable operation of the receiving‐end power grid after suffering from large power shortage. Its application in the current power system is divided into two categories [6, 7]: (a) When the power angle instability caused by the DC closure fault of the UHV terminal power grid is caused, a part of the load is urgently removed to improve the transient stability of the system. (b) When UHVDC block fault occurs, the large power shortage will cause the shortage of frequency and voltage drop, and when the frequency/voltage down to a certain extent, the under frequency load shedding/under voltage load shedding is triggered, then the emergency load shedding measures will be taken to ensure the frequency and voltage stability of a power system.…”
Section: Introductionmentioning
confidence: 99%
“…Air conditioning is a typical type of thermal storage characteristic load. It is a hot topic in the current research to incorporate it into the power system scheduling control [1–9]. Primary frequency control, secondary frequency control as well as economic dispatch are researched in the literature.…”
Section: Introductionmentioning
confidence: 99%